EVALUASI KEBIJAKAN PENGENDALIAN BANGUNAN Dl KABUPATEN SLEMAN - Wawan Hariawan (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2009)
The implementation of 1MB Permit in Sleman just reached the number of ownership 28.65% from full scale building. This became the strong indication that 1MB permit in Sleman is not yet optimal in reaching the target. This research uses evaluation study to explain the three factors as the root causes of the policy optimalization. First, service. The research shows that there were still service uncertainty in aspects of time and expenses, limitation of officers, and complexity of the procedure. Second, society awareness. The society awareness was still low in acknowledge the benefit to have 1MB permit. This was caused by the ineffective socialization from the government. Third, law enforcement. The related law in establish the firm 1MB permit should be strengthen. There should be a clear reward and punishment involved in this case.